Pengaruh Terpaan Review Film Agak Laen di Tiktok terhadap Minat Menonton Pelajar SMKN 3 Depok - Nabilla Azzalia Nadeem; Nyoman Suardhita (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
TikTok is a social media platform dominated by Gen Z users. TikTok serves as an informative platform as well as a marketing and advertising medium. On TikTok, there are various contents including movie reviews. Movie review content on TikTok serves as informative content to provide information about the storyline of movies currently showing in theaters. This is often needed by individuals before watching a movie, to find out about the synopsis, characters, and ratings given. This research aims to determine the extent of the influence of Agak Laen's movie review content on TikTok on the interest in watching movies among students of SMKN 3 Depok. The research approach is quantitative with a survey method involving 94 respondents from SMKN 3 Depok based on calculations using the Slovin's formula. According to the research findings, it can be concluded that the influence of Agak Laen's movie review content on TikTok on the interest in watching movies among students of SMKN 3 Depok is 55,8%, with the remaining 44,2% influenced by other factors.